The Effect of Proposed Training Program Using Fins to improve Special Fitness in the Free Style Swimming - Esam Abu-Shihab; Iyad Al-Kassasbeh (My University, 2016)
This study aimed to identify The Effect of proposed Training Program using fins To Improve of Special Fitness (Speed, Speed-Endurance, Endurance) in the free style Swimming, The sample of the study consisted of 24 swimmers who are currently the team of the Civil defense in Aqaba. The researchers used the experimental method. The sample has been split into two equal groups, 12 students in each group. The statistical measures that were used included (T) Test, Wilcoxon Method Pairs Signed, The results showed statistically significant differences between the post measurmen of the experimental group and the control group. This was for the experimental group. The researchers recommends the proposed training program is accredited as a way to Improve the the speed and speed-endurance, and endurance for swimmers, especially in the early age groups.

هدفت هذه الدراسة التعرف إلى أثر البرنامج التدريبي المقترح باستخدام الزعانف على تحسين بعض عناصر اللياقة البدنية الخاصة (السرعة، تحمل السرعة، التحمل) في السباحة الحرة، وتكونت عينة الدراسة من (24) سباحاً، تم تقسيمهم الى عينتين متكافئتين، (12) سباحا في كل مجموعة، تم اختيارهم بالطريقة القصدية من مرتبات الدفاع المدني فرع العقبة، واستخدم الباحثان المنهج التجريبي بطريقة المجموعة التجريبية والمجموعة الضابطة، حيث تم استخدام اختبار (ت) للعينات المستقلة للكشف عن الفروق بين المجموعتين الضابطة والتجريبية في التطبيق البعدي وكذلك التطبيق القبلي واختبار ويلكوكسون (Wilcoxon Method Pairs Signed) للعينات المرتبطة للكشف عن الفروق بين قياس الاختبار القبلي والبعدي للمجموعة التجريبية وكذلك المجموعة الضابطة، وأظهرت النتائج وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α ≤0.05) في القياسات البعدية بين المجموعتين التجريبية والضابطة ولصالح المجموعة التجريبية، وأوصي الباحث باعتماد البرنامج التدريبي المقترح كوسيلة للارتقاء في عناصر السرعة وتحمل السرعة والتحمل لسباحة الحرة.
أثر برنامج تدريبي مقترح باستخدام الزعانف على تحسين بعض عناصر اللياقة البدنية الخاصة في السباحة الحرة